2017
DOI: 10.4143/crt.2016.214
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Notch1 Signaling in Anaplastic Thyroid Carcinoma

Abstract: PurposeThe Notch signaling pathway is widely expressed in normal, reactive, and neoplastic tissues; however, its role in thyroid tissues has not been fully elucidated. Therefore, this study was conducted to characterize the expression of the Notch signaling pathway in papillary thyroid cancer (PTC) cells and anaplastic thyroid cancer (ATC) cells.Materials and MethodsExpression of activated Notch1 in ATC and PTC paraffin-embedded tissues was determined by immunohistochemistry. The small interfering RNA techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…By contrast, Kim et al . reported that the expression of activated NOTCH1 was higher in ATCs than in PTCs indicating a role of this pathway in aggressive evolution of thyroid cancer (19). According to these authors, inhibition of NOTCH1 significantly reduced proliferation and migration of ATC cells, but not PTC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Kim et al . reported that the expression of activated NOTCH1 was higher in ATCs than in PTCs indicating a role of this pathway in aggressive evolution of thyroid cancer (19). According to these authors, inhibition of NOTCH1 significantly reduced proliferation and migration of ATC cells, but not PTC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, Kim et al . postulated that NOTCH signaling influences the malignant potential of thyroid cancer and observed a NOTCH1-dependent reduction of epithelial-mesenchymal transition (EMT) and cancer stem cells markers in anaplastic tumors (19). In parallel, the expression of NOTCH1 receptor seems to be related to tumor invasiveness in PTC, and it has been proposed as molecular marker of poor prognosis (20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Kim et al demonstrated that the activated Notch-1 expression was higher in cases of ATC than in cases of PTC. Inhibiting Notch-1 significantly reduced the proliferation and migration of ATC cells, but not that of PTC cells [ 150 ]. In addition, inhibiting Notch-1 in ATC cells drastically reduced the expression of key markers representing epithelial to mesenchymal transition and cancer cell stemness.…”
Section: Non-genetic Heterogeneity Of Thyroid Cancermentioning
confidence: 99%
“…In addition, inhibiting Notch-1 in ATC cells drastically reduced the expression of key markers representing epithelial to mesenchymal transition and cancer cell stemness. Conversely, changes in the expression of these markers were not observed in PTC cells when the Notch-1 inhibition was applied [ 150 ]. This study demonstrated the different roles of Notch-1 expression in cancer cell aggressiveness between ATC and PTC, suggesting the heterogeneity of CSCs in thyroid cancer.…”
Section: Non-genetic Heterogeneity Of Thyroid Cancermentioning
confidence: 99%
“…and survival of normal cells or cancer cells in various cases. Notch signaling transduction consists of four Notch receptors (Notch 1, 2, 3 and 4) and five ligands [Delta 1, 3, 4 and Jagged (Jag) 1 and 2] (8). The Notch signaling pathway has been revealed to contribute to the progression of several cancers, including the proliferation, invasion and apoptosis of cancer cells (9,10).…”
Section: Effect Of Mir-449a-mediated Notch Signaling Pathway On the Pmentioning
confidence: 99%